THE REALIZATION OF E-BOOKS FOR TEACHING AS REFLECTED BY EFL TEACHERS OF ISLAMIC JUNIOR HIGH SCHOOL (MTs) - Priajana, Nana; Baehaqi, Luqman (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2012)
This study was aimed at processing empirical data to know the realization e-book program in EFL teaching and learning process as reflected by English teachers of Islamic Junior High School (MTs) in Indonesia. It is a descriptive research of which the approach is a cross sectional survey. The result of this study was expected to be the basis for the government to re-evaluate the implementation of the national project of School Electronic Books (BSE). Based on the result of data analysis, the program of e-books should be revised as considering several factors affecting its insufficient use by the EFL teachers of MTs. The use of E-book in teaching and learning in Indonesia EFL classroom had been beyond the teachersâ outlook. It revealed that e-book and its advantages were not well recognized by many teachers of MTs in Indonesia because of lack awareness of rapid growth of technology and information in this case the use of internet.Keywords: e-book, teaching and learning, program, implementation